Incremental Digital Transformation in Finance: Creating an Unstoppable DX Ratchet - Baber, William W.; Samy, Aya; Ojala, Arto (Springer, 2023)
Due to the increasing digitalization of business activities, many organizations are going through powerful Digital Transformation (DX). Surviving in the market competition requires changes, not only in technology, but also in organization structures. This brings new opportunities and challenges. In some sectors, like the highly regulated financial industry, this is even more critical than in IT or manufacturing firms. If a transformation project goes poorly, financial institutions might face catastrophic outcomes that will impact a large population and impact severe economic harm. For this reason, this study investigates DX of a major Japanese banking institution. We were especially interested in antecedents, barriers, and lessons learned during the DX process. To collect empirical data, we conducted a total of four interviews with the key decision-makers involved with the process. We found eight barriers and nine ways they are being overcome. A one-way ratchet that moves incrementally toward digitalization and transformation along with satisfaction about successes appear to be the most important methods to overcome barriers to DX.
Keywords: Digital Transformation (DX); Finance; Banking; Innovation; Japan; fi=Kansainvälinen liiketoiminta|en=International Business|